Self-Assembly of Solution-Processable Polyindole via Langmuir-Blodgett Technique: An Insight to Layer-Dependent Charge Transport and Electronic Parameters - Mishra R.; Pandey R.K.; Upadhyay C.; Prakash R. (My University, 2025)
Ordering of polymer chains at molecular level using a suitable post-synthesis fabrication technique is highly motivating towards enhancement in performance of organic electronic devices. Here, we report the formation of stable, large area self-assembled Langmuir-Blodgett (LB) films of unsubstituted polyindole (PIn) without aid of any surfactant. Pressure vs Area (π-A) isotherm for PIn is studied prior to device fabrication. Investigation of film uniformity via atomic force microscopy and scanning electron microscopy justified 30 mN/m as optimum surface pressure for depositing large area PIn LB films. Self-assembly in LB film is confirmed by absorption and Raman spectroscopy before device fabrication. A layer dependent charge transport of LB film of PIn is studied via current density (J)–voltage (V) characteristics and subsequently various device parameters are extracted using Schottky diode configuration of sandwiched structure Al/PIn LB film/ITO. A deviation in ideality factor, rectification ratio, current density and barrier height is observed for different number of layers. The electrical characteristics are also discussed taking into account the absorption spectra, Raman spectra, surface morphology, topography, barrier height. This study shows enormous potential for the fabrication of ordered PIn polymer on large area based electronic device application. © 2017 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim